Electrical Design and Construction of 3 Axis CNC Plasma Metal Cutting Machine - Zain, Khairil (Jurnal Teknik Mesin dan Mekatronika (Journal of Mechanical Engineering and Mechatronics), 2023)
Abstract. Computerized Numerical Control (CNC) is one of the developments in machining technology that is operated automatically which can support the demand for a product that has a complex shape, high accuracy and can work on objects that cannot be done with conventional machining. The design of the CNC 3 Axis machine is carried out with a design process to determine machine dimensions, determine calculations to determine motor requirements specifications. Followed by electrical wiring design to select the specifications of the controller used, and continued with testing the precision of the tool when testing the tool. The results of the design of this tool use Mach3 software as a machine controller and use a stepper motor as a motor drive. 3 Axis (X, Y and Z) Plasma CNC Machine (WCM) Design Using a Mach3 PC Base Stepper Motor that the controller system using Mach3 software has easy configuration because there is an auto tuning feature on each axis to determine distance precision. Using Mach3 software does not require a lot of cost because it can be downloaded on the internet.Keywords: CNC, Fabrication, Plasma Cutting Machine, Design and Build, Mach3